A Review of Aerosol Generation Mitigation in International Dental Guidance - Robertson, Clare; Clarkson, Jan E.; Aceves-Martins, Magaly; Ramsay, Craig R.; Richards, Derek; Colloc, Thibault (International dental journal, 2022)
The coronavirus disease 2019 (COVID-19) led to the worldwide closure of dental practices or reduction of dental services. By the end of April 2020, governments and professional organisations were publishing recommendations or guidance for the reopening/restructuring of dental services. The aim of this study was to assess how dental aerosol-generating procedures (AGPs) were defined in international dental guidelines, what mitigation processes were advised, and whether they were linked to COVID-19 epidemiology. Electronic searches of a broad range of databases, along with grey literature searches, without language restriction were conducted up to 13 July 2020. Recommendations for the use of face masks and fallow times with patients without COVID-19 were assessed against the deaths per 1 million population in the included countries and country income level using Pearson Chi-squared statistics. Sixty-three guidance documents were included. Most (98%) indicated that AGPs can be performed with patients without COVID-19 with caveats, including advice to restrict AGPs where possible, with 21% only recommending AGPs for dental emergencies. Face masks were recommended by most documents (94%), with 91% also specifying the use of goggles or face shields. Fallow periods for patients without COVID-19 were mentioned in 48% of documents, ranging from 2 to 180 minutes. There were no significant differences in recommendations for face masks or fallow time in patients without COVID-19 by country death rate (P = .463 and P = .901) or World Bank status (P = .504 and P = .835). Most documents recommended procedural or environmental mitigations such as preprocedural mouthwash (82%) and general ventilation (52%). Few documents provided underpinning evidence for their recommendations. While the amount of high-quality direct evidence related to dentistry and COVID-19 remains limited, it is important to be explicit about the considered judgements for recommendations as well as generate new evidence to face this challenge.